Low molecular weight heparin once versus twice for thromboprophylaxis following esophagectomy: a randomised, double-blind and placebo-controlled trial - Song, Jie-Qiong; Xuan, Li-Zhen; Wu, Wei; Huang, Jun-Feng; Zhong, Ming (Journal of Thoracic Disease, 2015)
Background: Venous thromboembolism (VTE) remained common complication following surgical resection of esophageal cancer. In this prospective randomized double-blind placebo-controlled trial (NCT01267305), we aim to compare the safety and efficacy between low molecular weight heparin (LMWH) once-daily (QD) and twice-daily (BID) for the prophylaxis of VTE following esophagectomy. Methods: During August 2012 to July 2013, patients underwent esophagectomy were randomly assigned to nadroparin calcium QD (4,100 AxaIU qd + placebo qd, group QD), or nadroparin calcium BID (4,100 AxaIU q12h, group BID) in the prophylaxis of VTE. All patients received thrombelastography (TEG) before and 0/24/48/72 hours after operation. Daily vascular ultrasound of lower extremities was followed during the first 7 postoperative days to confirm the suspected deep venous thrombosis (DVT). Cumulatively postoperative chest drainage at 72 hours after the surgery was collected to identify the difference in volume and red blood cell (RBC) counts between the two groups. Any bleeding events and thromboembolic events were also documented. Results: A total of 117 patients were enrolled in this study, and 111 eligible patients were randomly assigned (group QD: 55 patients; group BID: 56 patients). Patients’ clinical features were close between the two groups. TEG analysis [R time, K time, alpha angel and maximum amplitude (MA)] before and instantly after operation showed nearly identical results. However, compared with group QD, all TEG measurements of 24/48/72 hours postoperatively showed significantly prolonged R time and K time, and decreased alpha angel in group BID. In ultrasound follow-ups, a total of four cases of DVT (four cases in group QD and no case in group BID) were found in this cohort (7.27% versus 0%, P=0.046), and one case of pulmonary embolism (PE) (in group QD) was observed. The incidence of VTE was lower in group BID (9.09% versus 0%, P=0.032). At 72 hours after surgery, the cumulative volume of chest drainage were close between these two groups (1,001.39±424.58 versus 1,133.61±513.93 mL, P=0.406). RBC counts in chest drainage were also identical between two groups [(2.56±1.98)×105 versus (2.71±4.67)×105, P=0.61]. No patient died due to VTE or bleeding events. Conclusions: For the prophylaxis of VTE, BID LMWH provided more potent efficacy and equal safety when compared to QD LMWH in patients undergoing selective esophagectomy. Further study based on larger population is required to confirm these findings.